Analysis of Factors Affecting Intelligent-TPACK in the Faculty of Economics and Business Lecturers State University of Surabaya - Muhaimin, Ahmad Dicky; Pahlevi, Triesninda (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This research analyses the factors influencing Intelligent-TPACK (Technological Pedagogical Content Knowledge with AI) in FEB lecturers at the State University of Surabaya. This research uses a quantitative descriptive approach. The research population consisted of 155 respondents, and 112 respondents were taken as samples using a simple random sampling technique, which was calculated using the Slovin formula with an error rate of 5%. The research questionnaire used was adapted from the Intelligent-TPACK scale. Primary research data was obtained directly from questionnaires distributed to the sample, and secondary data was obtained from literature reviews of previous research and other relevant reading sources that supported the research. Data analysis was carried out using PLS-SEM with the help of SmartPLS 4.1 software to test the outer and inner models and the significance of hypothesis support. The research results show that five factors influence Intelligent-TPACK in FEB UNESA lecturers, including Intelligent-TK (lecturer's knowledge of AI tools and systems), Intelligent-TPK (lecturer's understanding of the pedagogical role of AI tools), Intelligent-TCK (lecturer's knowledge regarding the use of AI tools in their teaching field), ethics (lecturers' assessment of ethical aspects in using AI tools), and Intelligent-TPACK (lecturers' knowledge and skills in integrating AI pedagogically and ethically in teaching). The findings of this research show that Smart-TK has a positive and significant influence on Smart-TPK, Smart-TCK, and Ethics. Intelligent-TPK and Intelligent-TCK both make positive and significant contributions to Intelligent-TPACK, and Ethics assessments have a positive and significant influence on Intelligent-TPK, Intelligent-TCK, and Intelligent-TPACK for FEB lecturers at the State University of Surabaya.